2016
DOI: 10.1038/ejhg.2016.130
|View full text |Cite
|
Sign up to set email alerts
|

Variants in SKP1, PROB1, and IL17B genes at keratoconus 5q31.1–q35.3 susceptibility locus identified by whole-exome sequencing

Abstract: Keratoconus (KTCN) is a protrusion and thinning of the cornea, resulting in impairment of visual function. The extreme genetic heterogeneity makes it difficult to discover factors unambiguously influencing the KTCN phenotype. In this study, we used whole-exome sequencing (WES) and Sanger sequencing to reduce the number of candidate genes at the 5q31.1-q35.3 locus and to prioritize other potentially relevant variants in an Ecuadorian family with KTCN. We applied WES in two affected KTCN individuals from the Ecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 34 publications
3
15
0
Order By: Relevance
“…17 In chronic dry eye patients, SLC is attributed to the increase of mechanical friction between the eyelid and the ocular surface. 22,23 However, this has also been found with other conditions, such as eye surgery and is usually associated with chronic mechanical irritation or trauma. 17 Some hypotheses regarding the cause of keratoconus related to eye rubbing are the release of inflammatory mediators, 26 increased corneal temperature (thereby explaining corneal deformation), 29 epithelial thinning, large intraocular pressure spikes, and others.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…17 In chronic dry eye patients, SLC is attributed to the increase of mechanical friction between the eyelid and the ocular surface. 22,23 However, this has also been found with other conditions, such as eye surgery and is usually associated with chronic mechanical irritation or trauma. 17 Some hypotheses regarding the cause of keratoconus related to eye rubbing are the release of inflammatory mediators, 26 increased corneal temperature (thereby explaining corneal deformation), 29 epithelial thinning, large intraocular pressure spikes, and others.…”
Section: Discussionmentioning
confidence: 91%
“…5 Therefore, it has been postulated as a multifactorial disease. 4,5,7,22,23 Multiple studies have revealed an association with certain genes; 22,24 however, it currently cannot be diagnosed based on genetic screening. 23,24 Eye rubbing has been postulated as a significant risk factor by several authors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several candidate genes for KTCN have also been identified using Sanger sequencing or next generation sequencing (NGS) including VSX1, SOD1, and DOCK9 or SKP1, MPDZ, FLG, PPIP5K2, and PCSK1, respectively. [26][27][28][29][30][31][32] However, variants detected in those genes were present in a small fraction of KTCN patients or particular populations only.…”
Section: Introductionmentioning
confidence: 98%
“…Linkage studies also have led to the identification of a few potential KTCN candidate genes, including SPARC, IL1RN, and SKP1. These genes encode a cysteine-rich acidic matrixassociated protein, IL1 receptor antagonist, and S-phase kinase-associated protein 1 that are known to be involved in the extracellular matrix (ECM) formation, immune response, and ubiquitination, respectively (Bisceglia et al, 2009;Nowak et al, 2013;Karolak et al, 2016a).…”
Section: Introductionmentioning
confidence: 99%